A study on Electron Oscillations in the Magnetosheath of Mars with Mars Express observations. Issue Volume 12:Issue S328(2016) (12th September 2017) - de Souza, Adriane M.; Echer, Ezequiel; Bolzam, Mauricio J. A.; Fränz, Markus
Abstract: Wavelet analysis was employed to identify the major frequencies of low-frequency waves present in the Martian magnetosheath. The Morlet wavelet transform was selected and applied to the electron density data, obtained from the Analyzer of Space Plasmas and Energetic Atoms experiment (ASPERA-3), onboard the Mars Express (MEX) spacecraft. We have selected magnetosheath crossings and analyzed electron density data. From a preliminary study of 502 magnetosheath crossings (observed during the year of 2005), we have found 1409 periods between 0.005 and 0.06 Hz . The major frequencies observed were in the range 0.005-0.02 Hz with 58.5% of the 1409 frequencies identified.